2022
DOI: 10.3390/ijms23116084
|View full text |Cite
|
Sign up to set email alerts
|

New Potential Agents for Malignant Melanoma Treatment—Most Recent Studies 2020–2022

Abstract: Malignant melanoma (MM) is the most lethal skin cancer. Despite a 4% reduction in mortality over the past few years, an increasing number of new diagnosed cases appear each year. Long-term therapy and the development of resistance to the drugs used drive the search for more and more new agents with anti-melanoma activity. This review focuses on the most recent synthesized anti-melanoma agents from 2020–2022. For selected agents, apart from the analysis of biological activity, the structure–activity relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 149 publications
(198 reference statements)
0
6
0
Order By: Relevance
“…Prior to this study, very little was known about whether extracts of Sinningia plants can suppress the growth of cancer cells. Malignant melanoma is the most dangerous and the most common type of skin cancer [ 26 ]. Considering that many natural products exhibit anticancer properties towards skin cancers, the highly metastatic B16F10 melanoma cells were selected for this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to this study, very little was known about whether extracts of Sinningia plants can suppress the growth of cancer cells. Malignant melanoma is the most dangerous and the most common type of skin cancer [ 26 ]. Considering that many natural products exhibit anticancer properties towards skin cancers, the highly metastatic B16F10 melanoma cells were selected for this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds containing phthalimide moieties have been observed to have potential anti-tumor activity. 22–24 Moreover, cyclic peptides exhibit more stable chemical properties than linear cyclic peptides in a variety of chemical and biological environments, and thus have better pharmacological properties. Therefore, the cytotoxicity of all synthesized linear peptide precursors ( 1a–14a ) and cyclic peptides ( 1–14 , Scheme 1) was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Given the upregulated nature of this process as a result of proliferation, DHODH inhibitors represent a new hope for targeted therapy for melanoma [ 94 ]. Our review of the literature on the latest anti-melanoma agents revealed that the phenoxy derivatives we have obtained are among the first in recent years [ 95 ]. The most active compound bore a 2-iodophenyl substituent [ 93 ].…”
Section: Novel Agent With the Terminal Phenoxy Group From The Most Re...mentioning
confidence: 99%